Improving critical thinking skills in business mathematics lectures through problem base learning - Hidayat, Rachmat; Apriwandi, Apriwandi; Christine, Debbie (Jurnal Mantik, 2024)
Students' mathematical critical thinking skills have not been optimally developed. Skill development is done through PBL (Problem Base Learning) strategy. The study aims to determine the impact of PBL on critical thinking skills using an experimental design with a control group. Business students who were taking Business Mathematics courses in Bandung city became the population. The research sample was 107 first semester business students who were taking mathematics courses. The sample was randomly selected by class. The research instrument was developed by the researcher and was in the form of a test with moderate difficulty and good differentiating power, high validity and reliability. Data were analyzed by one and two-way ANOVA. The results of the study: (1) the critical thinking ability of students who learn through PBL is better than those who learn conventionally, (2) the critical thinking ability of students with high, medium and low initial abilities who learn through PBL is not better than those who learn conventionally, (3) the effect of learning on critical thinking ability does not depend on initial ability, (4) the attitude of students who learn through PBL is more positive than those who learn conventionally.